A escola e o bairro : percepção ambiental e interpretação do espaço de alunos do ensino fundamental - Mansano, Cleres do Nascimento (2006)
From July to September 2005, during Geography classes in a group of 40 students from apublic school in the city of Maringá, Paraná - Brazil, an investigation was carried out to check the students' environmental perception concerning their school and neighborhood. The goal was to interpret their perceptions of the environment from representations of the concept of "landscape". The research was carried out in seven steps, comprising theoretical and field classes. At first, activities were developed in which they could debate and represent through drawings "the beautiful and the ugly landscape" from school and neighborhood. During the research, through activities as questionnaire and composition, it was possible to understand students' environmental perception relating to the focused area as well as their attitudes and values. It was also developed activities to make possible to the students observe and represent their mental images from the covered space through drawings and maps. The photography was an important strategy, making possible to the student represent the school and surrounding areas even if he had not the ability to draw. Among the activities, the students worked with articles which provided them theoretical information to build their own knowledge based on scientific knowledge. We observe that, in the beginning of research, for most part of the students, the "beautiful landscape" was related to natural elements and the "ugly landscape" was related to other elements, generally associated with anthropic action. It was also observed that they presented difficulties to detect the multi-relations that exist in the landscape. However, during the research, most of the students' environmental perception became broader, being able to decode the space in which they lived. They presented an evolution in the way of representing "the lived landscape", perceiving elements not perceived before.